A CASE STUDY OF ACADEMICALLY HIGH ACHIEVED STUDENTS IN KSEEB EXAMINATION - N, Dandinker Suryakant (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Education aims to foster the all-round development of students, nurturing their intellectual, emotional, and social growth. Among the students, a notable number are excelling in KSEEB board examinations, showcasing their potential and determination. However, it is observed that while some students’ exhibit exceptional brilliance and benefit from strong parental support, others with average IQ levels and challenging socio-economic backgrounds also perform commendably. This raises important questions about the factors contributing to academic success and the support systems required to enable such achievements. Gulbarga, an underdeveloped city with a unique socio-cultural and economic context, provides an interesting backdrop for this investigation. Given its challenges, the academic success of students in this region holds particular significance. To delve deeper into this phenomenon, the investigator employed a case study method, which allows for a holistic and in-depth exploration of the variables affecting student performance. The findings highlight several critical aspects. First, the role of parents is pivotal in shaping a child's educational journey. Parents are encouraged to create a supportive and nurturing environment at home, which is conducive to learning. A stable and encouraging atmosphere can significantly boost a student’s confidence and focus. Additionally, the role of teachers cannot be overstated. Educators should strive to identify the individual needs and challenges of their students. By providing tailored support and fostering a positive learning environment, teachers can enhance both the confidence and performance levels of their students. Ultimately, a collaborative effort between parents, teachers, and the broader community can empower students to overcome obstacles and excel academically, regardless of their socio-economic background.